The cauliflower dilemma!. (9th April 2019) - Gupta, Gaurav; Kumar, Vikas; Paruthi, Mandakini; Mendiratta, Priyam
The present case shows the plight of small farmers during demonetisation drive in India. This unprecedented move by the Government of India has led the entire economy in a state of sudden shock and small farmers found themselves, very much helpless and confused. The case visits the production cycle of cauliflower from the perspective of a small farmer and traverses the complete journey of money borrowing for different phases of agricultural production. Options available to the farmers have been described with a comparative perspective. Both the formal and informal aspects of agricultural business have been presented in a typical Indian scenario with relevant stakeholders. The case presents a very practical perspective of small farmers in India, hence ideal for understanding this most significant activity of Indian activity.